Elevated expression of Tie1 is accompanied by acquisition of cancer stemness properties in colorectal cancer. (2nd May 2017) - Torigata, Miku; Yamakawa, Daishi; Takakura, Nobuyuki
Abstract: The Tie receptors 1 and 2 (Tie1/2) play crucial roles in embryonic angiogenesis. Recent studies suggest enhanced expression of Tie1 in several types of cancer and negative correlations between Tie1 levels and clinical outcome. These observations suggest important functions of Tie1 not only for vascular formation but also in tumorigenesis. Ligands for Tie2, that is angiopoietins 1‐4, have been identified, but not for Tie1. To determine the molecular functions of Tie1, its detailed characterization in tumors would be helpful. Herein, we report that Tie1 is up‐regulated in colorectal cancer. Detailed analysis using tumor‐bearing models and immunohistochemistry combined with Flow cytometric analysis and cell sorting (FACS) revealed that Tie1 protein was expressed in a small population of malignant tumor cells. Intriguingly, Tie1 expression was observed and could be maintained only in vivo. Further analysis using sphere‐formation culture revealed that Tie1‐positive cells are enriched within the population of tumor cells with cancer stemness properties. Indeed, Tie1‐positive tumor cells derived from a murine model overexpressed Lgr5, a typical stemness marker for colorectal cancer. Our results provide a novel insight into Tie1 function in tumorigenesis and suggest clinical applications to target cancer stem cells. Abstract : We identified Tie1, a receptor tyrosine kinase frequently expressed on vascular endothelial cells, as a candidate molecule marking malignant cancer cells. Tie1 expression on cancer cells was associated with the presence of colorectal cancer stem cell molecule Lgr5. Sphere‐formation culture of cancer cells induced Tie1 expression and the cancer cells surviving after in vivo treatment with anticancer drugs strongly expressed Tie1.